KARAKTERISTIK SEGITIGA LUCAS - Siti Rahmah Nurshiami; Ari Wardayani; Kana Hasmi Setiani (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
Lucas triangle is an array of coeficients of a polynomial forming a pattern which is similar to Pascal triangle. This research studies Lucas triangle and its properties. The research results show that every row in Lucas triangle is begun by the number 1 and is ended by the number 2, the sum of the first n terms of number of 1th column is equal to the number at th row, 2nd column. Besides, the number at nth row and th column of Lucas triangle is for , the sum of the first n terms of number of jth column is equal to the number at th row, column for . The number of Lucas triangle is the sum of two number terms in preceded row, that is the number at th row, and the number at th row, . Then, the sum of coefficients of each row of Lucas triangle is . Full Article